Health promotion in primary care: How should we intervene? A qualitative study involving both physicians and patients - Cortada Josep M; Balagué Laura; Calderón Carlos; Sánchez Álvaro (BMC, 2011)
Abstract Background The effects of tobacco, physical exercise, diet, and alcohol consumption on morbidity and mortality underline the importance of health promotion and prevention (HPP) at the primary health care (PHC) level. Likewise, the deficiencies when putting such policies into practice and assessing their effectiveness are also widely recognised. The objectives of this research were: a) to gain an in-depth understanding of general practitioners' (GPs) and patients' perceptions about HPP in PHC, and b) to define the areas that could be improved in future interventions. Methods Qualitative methodology focussed on the field of health services research. Information was generated on the basis of two GP-based and two patient-based discussion groups, all of which had previously participated in two interventions concerning healthy lifestyle promotion (tobacco and physical exercise). Transcripts and field notes were analysed on the basis of a sociological discourse-analysis model. The results were validated by triangulation between researchers. Results GPs and patients' discourses about HPP in PHC were different in priorities and contents. An overall explanatory framework was designed to gain a better understanding of the meaning of GP-patient interactions related to HPP, and to show the main trends that emerged from their discourses. GPs linked their perceptions of HPP to their working conditions and experience in health services. The dimensions in this case involved the orientation of interventions, the goal of actions, and the evaluation of results. For patients, habits were mainly related to ways of life particularly influenced by close contexts. Health conceptions, their role as individuals, and the orientation of their demands were the most important dimensions in patients' sphere. Conclusions HPP activities in PHC need to be understood and assessed in the context of their interaction with the conditioning trends in health services and patients' social micro-contexts. On the basis of the explanatory framework, three development lines are proposed: the incorporation of new methodological approaches according to the complexity of HPP in PHC; the openness of habit change policies beyond the medical services; and the effective commitments in the medium to long term by the health services themselves at the policy management level.